A leap towards changing gender dynamics in oncology leadership$nan ESSO-EYSAC initiative - Kaul, Pallvi; Caballero, Carmela; Brandl, Andreas; Garg, Pankaj Kumar (European journal of surgical oncology, 2023)
Despite the importance of diversity for the success and survival of biological and social systems, women are underrepresented in leadership positions, particularly in the medical field. Data from seven internationally renowned academic associations in surgical, medical, and radiation oncology show that women's representation in leadership roles is only 11%, with no individual society exceeding 20%. Possible justifications for the underrepresentation of women include unconscious biases and societal norms. Fortunately, a notable development in the form of an increased number of women attaining leadership positions in many major professional societies has emerged over recent times, thereby reflecting a positive transformation in the direction of gender equality. The authors recommend organizational interventions such as mentorship, leadership development programs, and national-level initiatives with global collaboration. The oncology community must promote a culture of cooperation and gender equality to ensure equitable opportunities for women in all aspects of life, including professional hierarchy.